Potassium Monitoring in Young Women Taking Spironolactone for Acne is Unnecessary. (June 2015) - Carter, David
Abstract : According to this study: Spironolactone, an effective and inexpensive treatment for hormonally mediated acne, is safe for healthy women to use without being monitored for hyperkalemia. Of 1, 802 serum potassium measurements that were obtained, only 13 (0.72%) indicated hyperkalemia—and all 13 cases were mild.